The Study of Medicinal Plant Diversity at Opak Watershed, Special Region Yogyakarta - Djoko Santosa; Subagus Wahyuono; Sugeng Riyanto; S M Widyastuti (Majalah Farmaseutik, 2017)
Research on the diversity of medicinal plant at  Opak watershed has been done. The purpose of this study is to determine the composition of medicinal plants, distribution and development potential as herbs raw materials. The study area is divided into 6 locations, namely Cangkringan subdistrict (CNK), Ngemplak (NPL), Prambanan (PRB), Kalasan (KLS), Imogiri (IMO), and Pundong (PDO). Each location is placed 30 plots by squares measuring 2x1 m. In the plot is calculated the number of species and individual of each  species. The results showed there were  79 speies of plants are grouped into 27 families. Based on the type contribution in the environment and the literature study of  Eupatorium riparium, Andrographis paniculata, and Scoparia dulcis are potential plants to be developed as raw materials of herbs medicine.